Sustainable Growth Rate: Liquidity & Profit Margin with Firm Size as Moderating Variable - Teguh Erawati; Putri Yulianti Lestari; Reni Listyawati (Proceeding International Conference on Accounting and Finance, 2025)
This study examines the factors that influence Sustainable Growth Rate (SGR) as a key indicator in maintaining financial performance and business sustainability. This research focuses on profit margin, liquidity ratio, and firm size as determinants in achieving SGR. This study focuses on manufacturing companies in Indonesia. The results show that a planned and measurable growth strategy is very important in maintaining business sustainability and attracting investors. This study uses purposive sampling as a data collection technique, while multiple linear regression is the analysis method. This study uses 370 data from manufacturing companies from 2019 to 2023. In 2019 to 2023, the selected manufacturing businesses are those that have a stable history of Liquidity Ratio and Profit Magin sharing. The company's sustainable growth rate (SGR) is measured by retained earnings compared to equity. SGR measurement uses company profits. From the research results, the Profit Margin policy has a negative effect on SGR, Liquidity Ratio has a positive effect on SGR and Firm Size does not moderate Liquidity Ratio and Profit Margin on SGR.